Consuming Germany in the Cold War - Crew, David F. 1946- Hrsg (Leisure, consumption and culture, 2003)
Consuming Germany in the Cold War : consumption and national identity in East and West Germany, 1949-1989, an introduction / David F. Crew -- "A world in miniature" : the Leipzig Trade Fairs in the 1950s and East German consumer citizenship / Katharine Pence -- On the seam between socialism and capitalism : East German fashion shows / Judd Stitziel -- The order of substitutes : plastic consumer goos in the Volkswirtschaft and everyday domestic life in the GDR / Eli Rubin -- Born again in the gospel of refreshment? : Coca-colonization and the re-making of postwar German identity / Jeff R. Schutts -- Miracles for sale : consumer displays and advertising in postwar West Germany / S. Jonathan Wiesen -- Drugs, consumption and internationalization in Hamburg, 1960-1968 / Robert P. Stephens